Households' rice demand response to changes in price, income and coping strategies during food inflation in Nigeria: Evidence from Oyo State - Abiodun Elijah Obayelu; Adeola Oluwaseun Wintola; Elizabeth Olufunmilayo Ayokunnumi Oluwalana (Italian Review of Agricultural Economics (REA), 2022)
Food price is a main driver of inflation that erodes the purchasing power of households. The study examined demand response to changes in price of rice during food price inflation in Nigeria using sampled households from Oyo State. A multi-stage sampling procedure was used to select 174 households for the study. Primary data were obtained on types of rice, frequency and quantity bought, reasons for demand, price variations and coping strategies. Descriptive statistics and Quadratic Almost Ideal Demand System (QUAIDS) that take into account the non-linear impact of income changes was used for data analysis. Over 70% of households' demand was for imported long grain rice, local brown and wet grain rice and local brown and dry grain rice. The expenditure elasticities of both local short brown wet rice (LSBWR) and imported short grain rice (ISGR) was positive and <1 indicating that they were normal and necessary food items. Strategies mainly used to cope with rice price and households' income changes include: substitution of rice with other food types, preparation of rice with other foods to reduce quantity of rice in meals and reduction of rice demand. Even though price intervention may not lead to a significant effect on rice demand, an improvement in technology will lead to reduction in the cost of rice production and eventually reduce the price of local rice, enhance high demand and encourage producers to increase production.
Keywords: D01; D11; D12; D15; E31; H31; J28; R22; 330; Consumer Responsiveness; compensated elasticity; uncompensated elasticity; LSBWR; LSBDR; ISGR; ILGR; QUAIDS